COMMERCIAL DISPUTE RESOLUTION: HAS ARBITRATION TRANSFORMED NIGERIAâS LEGAL LANDSCAPE? - Olusola, Olujobi J.; Oyewunmi, Olabode A.; Adeniji, Adenike A.; Oyewunmi, Adebukola E. (Universitas Tadulako, 2018)
The adoption of arbitration in the light of its well established attributes promotes confidence levels in the general businesses environment, enhances institutional trust, whilst also developing practical compromise resolution mechanisms. Hence, arbitration is usually deployed as a preferred option for resolving modern commercial disputes. However, Nigeria, a developing economy has not matched policy intent with commercial realities, particularly in terms of broad based integration and utilization of arbitral tools. This trend is not sustainable in the light of the renewed efforts to promote enhanced justice delivery; lower administrative costs and the urgent need to optimize the capabilities of the judicial arm of government. The paper assessed specific arbitral provisions of selected, State High Court Civil Procedures Rules, and on this basis critiqued the arbitral visibility and incorporation relative to established legal processes. Amongst other salient issues, a robust application of arbitration is recommended especially in view of the peculiarities of Nigeriaâs legal processes, judicial institutions, evolving political and social-economic indicators.Â Â Â Â Â Â Â